NSG2: a promising prognostic marker shaping the immune landscape of breast cancer - Li, Xuan; Gu, Qiming; Sun, Pingping; Yang, Lei; Zhang, Xiaojing; Lu, Bing; Ni, Qichao (Frontiers in Immunology, 2024)
Background: Breast cancer (BC) remains a significant health issue globally and most common cause of mortality in women. Enhancing our understanding on biomarkers may greatly improve both diagnostic and therapeutic approaches to this disease. Methods: We retrospectively assessed tumor samples from 228 BC cases and 51 normal samples, alongside relevant clinical data. Neuronal vesicle trafficking associated 2(NSG2) expression was evaluated through bioinformatics and multiplex immunohistochemistry. Associations between NSG2 expression, tumor-infiltrating immune cells (TIICs), immune checkpoints, and clinical outcomes were investigated. Results: NSG2 was present in both breast cancer cells and adjacent stromal cells. Increased NSG2 expression in cancer cells correlated with greater tumor size, distant metastasis, and more advanced clinical stages. Kaplan-Meier survival and multivariate analyses identified NSG2 expression in both cancer and stromal cells as an independent prognostic factor for breast cancer survival. Elevated NSG2 levels both in cancer and stroma cells were linked to increased CD4+ T, CD8+ T, and Lamp3+ dendritic cells infiltration in stromal regions (P < 0.05). Conversely, the expression of NSG2 in the stroma was negatively correlated with CD20+ B cells (P < 0.05). Additionally, NSG2 expression was found to be associated with CTLA-4 levels (P < 0.05). Conclusion: NSG2 seems to be a significant component of the BC immune microenvironment and may serve as an important prognostic marker.